Analysis of Digital Customer Communities in terms of their interactions during the first wave of the COVID-19 pandemic - Pollák František (Management şi Marketing, 2021)
The COVID-19 pandemic has redefined procedures in every business sector. In the first half of 2020, companies had to face an unexpected and unpredictable situation that resulted in both threats and opportunities in real time. Almost overnight, brick-and-mortar establishments of most stores closed, and the dominant part of transactions and activities moved from offline to the online environment. The main goal of the paper is to identify changes in the interactions of digital customer communities of selected e-business representatives in the Czech market. Within a sample of almost one and a half million Facebook users, during the first spring COVID-19 lockdown (March to May 2020), the interactions of the five largest Czech e-shops and their customers were recorded on a daily basis. The data were then subjected to a thorough statistical analysis in order to identify the specifics that resulted from the highly non-standard market situation. The results suggest that during the pandemic, there was a major reallocation of interactions in terms of their timing. Most interactions take place during the working week. From a day-to-day perspective, most of the interactions occur at around noon. In view of the findings, it can be stated that in order to maintain the competitiveness resulting from efficient management of corporate resources, it will be necessary to modify the usual procedures of e-marketing communication, as well as human resources management procedures in terms of the optimization of work of employees working from home.